Killers of the Flower Moon [compact disc, unabridged] : the Osage murders and the birth of the FBI - Grann, David (Books on Tape : Random House Audio, 2017)
Presents a true account of the early twentieth-century murders of dozens of wealthy Osage and law-enforcement officials, citing the contributions and missteps of a fledgling FBI that eventually uncovered one of the most chilling conspiracies in American history.